Conductive composition
By reasonably formulating solid and liquid epoxy resins, conductive particles and blocked isocyanate curing agents in the conductive composition, the problem that conductive compositions in the prior art are prone to pinholes after screen printing is solved, and excellent conductivity and appearance are achieved.
Patent Information
- Application Number
- CN202380063785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-06
- Publication Date
- 2025-04-18
AI Technical Summary
After screen printing, conventional conductive compositions tend to produce bubbles (pinholes) on the printing surface, affecting appearance.
The conductive composition containing 40 to 70 parts by mass of solid bisphenol-type epoxy resin and 30 to 60 parts by mass of liquid epoxy resin is used, and a conductive composition containing 1400 to 2500 parts by mass of conductive particles, 60 to 120 parts by mass of blocked isocyanate curing agent and an appropriate amount of solvent is used. The liquid epoxy resin contains free alicyclic epoxy resin and rubber modified epoxy resin.
Excellent conductivity and appearance after curing are achieved, the generation of pinholes is reduced, and the consistency and aesthetics of the printing surface are improved.
Smart Images

Figure HDA0005297275090000011 
Figure HDA0005297275090000012 
Figure HDA0005297275090000021
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive composition. Background Art
[0002] As a method for forming wiring on a substrate, a method of screen printing a conductive composition on a substrate is known. As a conductive composition used in such screen printing, Patent Document 1 discloses a heat-curable conductive paste composition containing a conductive powder, a thermosetting component, a curing agent, and a solvent. In this heat-curable conductive paste composition, as the conductive powder, a flaky powder and a spherical powder are used, and the thermosetting component is composed of the following three components A to C, and contains these components in a predetermined ratio.
[0003] Component A: an epoxy resin having a cyclic structure and having an epoxy equivalent of 160 to 400 and a viscosity at 25° C. of 3,000 to 55,000 mPa·s.
[0004] Component B: an epoxy resin having a cyclic structure and an epoxy equivalent of 140 to 300 inclusive and a viscosity at 25° C. of 30 to less than 3,000 mPa·s.
[0005] Component C: a resin that is a solid resin at 25° C. and is polymerized using bisphenols and epichlorohydrin.
[0006] In order to form wide wiring on a substrate, a plate is sometimes formed on a grid with a wide line width, and screen printing is performed using the plate. In this case, in conventional conductive compositions, bubbles (hereinafter sometimes referred to as pinholes) may be generated on the printed surface when the printing plate is removed from the substrate after the conductive composition is applied, and there is room for improvement in appearance.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2013-194169 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a conductive composition having both excellent conductivity and appearance after curing.
[0012] Solutions for solving problems
[0013] The present invention includes the following embodiments.
[0014] [1] A conductive composition comprising 1400 to 2500 parts by mass of conductive particles (B), 60 to 120 parts by mass of a blocked isocyanate curing agent (C), and a solvent (D) relative to 100 parts by mass of a binder component (A) comprising 40 to 70 parts by mass of a solid bisphenol epoxy resin and 30 to 60 parts by mass of a liquid epoxy resin, wherein the liquid epoxy resin comprises at least one selected from the group consisting of an alicyclic epoxy resin and a rubber-modified epoxy resin.
[0015] [2] The conductive composition according to [1], wherein the conductive particles (B) include spherical conductive particles and dendritic conductive particles.
[0016] [3] The conductive composition according to [1] or [2], wherein the liquid epoxy resin comprises an alicyclic epoxy resin and a rubber-modified epoxy resin.
[0017] Effects of the Invention
[0018] According to the conductive composition of the present invention, excellent conductivity and appearance after curing can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an X-ray transmission image (magnified 50 times) taken of the sample of Comparative Example 1-1.
[0020] Figure 2 This is an X-ray transmission image (magnified 50 times) taken of the sample of Comparative Example 1-2.
[0021] Figure 3 This is an X-ray transmission image (magnified 50 times) taken of the sample of Example 1-1.
[0022] Figure 4 This is an X-ray transmission image (magnified 50 times) taken of the sample of Example 1-2. DETAILED DESCRIPTION
[0023] Hereinafter, embodiments of the present invention will be described in more detail.
[0024] The conductive composition of the present embodiment contains 1400 to 2500 parts by mass of conductive particles (B), 60 to 120 parts by mass of a blocked isocyanate curing agent (C) and a solvent (D) relative to 100 parts by mass of a binder component (A) comprising 40 to 70 parts by mass of a solid bisphenol epoxy resin and 30 to 60 parts by mass of a liquid epoxy resin, wherein the liquid epoxy resin comprises at least one selected from the group consisting of an alicyclic epoxy resin and a rubber-modified epoxy resin.
[0025] Here, the solid epoxy resin refers to an epoxy resin that has no fluidity in a solvent-free state at room temperature (25° C.), and the liquid epoxy resin refers to an epoxy resin that has fluidity in a solvent-free state at room temperature (25° C.).
[0026] Examples of the solid bisphenol epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin. These may be used alone or in combination of two or more.
[0027] The epoxy equivalent of the solid bisphenol epoxy resin is not particularly limited, but is preferably 1,000 to 10,000 g / eq, and more preferably 3,000 to 10,000 g / eq.
[0028] In this specification, the epoxy equivalent of an epoxy resin refers to the mass of a resin containing one equivalent of epoxy groups measured in accordance with JIS K7236:2009 prepared based on ISO 3001 Plastics-Epoxy compounds-Determination of epoxy equivalent.
[0029] The liquid epoxy resin contains at least one selected from the group consisting of alicyclic epoxy resins and rubber-modified epoxy resins. Examples of the alicyclic epoxy resins include dicyclopentadiene epoxy resins, hydrogenated bisphenol A epoxy resins, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexylcarboxylate, ε-caprolactone-modified 3,4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 1,2,8,9-diepoxylimonene, tetrahydroindene diepoxide, and the like, and these may be used alone or in combination of two or more.
[0030] "Rubber modified epoxy resin" refers to an epoxy resin in which a rubber component is dispersed in a liquid epoxy resin. As the liquid epoxy resin, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, etc. can be cited, and they can be used alone or in combination of two or more. Among these, bisphenol A type epoxy resin is preferred. As the rubber component, for example, polybutadiene rubber (BR), acrylic rubber (ACM), silicone rubber, butyl rubber (IIR), isoprene rubber (IR), chloroprene rubber (CR), nitrile rubber (NBR), styrene butadiene rubber (SBR), ethylene propylene rubber (EPR), etc. can be cited, and they can be used alone or in combination of two or more. Among these, as the rubber modified epoxy resin, an epoxy resin modified by NBR (NBR modified epoxy resin) is preferred.
[0031] The liquid epoxy resin may contain liquid epoxy resins other than alicyclic epoxy resins and rubber-modified epoxy resins. Examples of such other liquid epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, phenol novolac epoxy resins, and glycidylamine epoxy resins.
[0032] The total content of the alicyclic epoxy resin and the rubber-modified epoxy resin in the liquid epoxy resin is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 100% by mass.
[0033] The epoxy equivalent of the alicyclic epoxy resin is not particularly limited, but is preferably 70 to 300 g / eq, more preferably 150 to 250 g / eq. The epoxy equivalent of the rubber-modified epoxy resin is not particularly limited, but is preferably 220 to 400 g / eq, more preferably 300 to 400 g / eq.
[0034] 100 parts by mass of the binder component (A) contains 40 to 70 parts by mass of the solid bisphenol epoxy resin and 30 to 60 parts by mass of the liquid epoxy resin, and more preferably contains 50 to 60 parts by mass of the solid bisphenol epoxy resin and 40 to 50 parts by mass of the liquid epoxy resin. When the amount of the solid bisphenol epoxy resin is 40 parts by mass or more, the amount of pinholes can be reduced and the appearance can be improved. In addition, when it is 70 parts by mass or less, the conductivity can be improved.
[0035] The ratio of the epoxy resin in the binder component (A) is particularly preferably 70 to 100% by mass, and most preferably 90 to 100% by mass.
[0036] Binder component (A) can contain solid epoxy resins other than solid bisphenol epoxy resins within the scope of not damaging the purpose of the present invention. As other solid epoxy resins, for example, spiro-type epoxy resin, naphthalene-type epoxy resin, biphenyl-type epoxy resin, terpene-type epoxy resin, glycidyl ether-type epoxy resins such as tris (glycidyloxyphenyl) methane, tetrakis (glycidyloxyphenyl) ethane, glycidylamine-type epoxy resins such as tetraglycidyl diaminodiphenylmethane, cresol novolac-type epoxy resin, phenol novolac-type epoxy resin, α-naphthol novolac-type epoxy resin, brominated phenol novolac-type epoxy resin, novolac-type epoxy resins, rubber-modified epoxy resins, etc. can be used. They can be used alone or in combination of two or more. In addition, the solid epoxy resin can also be dissolved in a solvent (D) described later for use.
[0037] The binder component (A) may contain components other than the epoxy resin within the scope of not damaging the purpose of the present invention. As components other than the epoxy resin, for example, alkyd resins, melamine resins, xylene resins, silicone resins, polyurethane resins, acrylic resins, etc. may be contained. Their content in the binder component (A) is preferably 30% by mass or less, more preferably 10% by mass or less. By using these resins, adhesion becomes good.
[0038] The content of the conductive particles (B) is not particularly limited and may be 1400 to 2500 parts by mass, but is preferably 1500 to 2500 parts by mass, and more preferably 1600 to 2400 parts by mass, based on 100 parts by mass of the binder component (A).
[0039] As the conductive particles (B), for example, copper particles, silver particles, nickel particles, silver-coated copper particles, gold-coated copper particles, silver-coated nickel particles, gold-coated nickel particles, silver-coated copper alloy particles, etc. can be cited. They can be used alone or in combination of two or more. As the conductive particles (B), at least one selected from the group consisting of silver particles, silver-coated copper particles and silver-coated copper alloy particles is preferred. The silver-coated copper particles are not particularly limited as long as they have a silver-containing layer of at least a portion of the copper particles and the coated copper particles. The silver-coated copper alloy particles are not particularly limited as long as they have a silver-containing layer of at least a portion of the copper alloy particles and the coated copper alloy particles. The content ratio of the silver-containing layer in the silver-coated copper particles and the silver-coated copper alloy particles is not particularly limited, and is preferably 4 to 24% by mass. The content of silver in the silver-containing layer is not particularly limited, and is preferably 90 to 100% by mass. The copper alloy particles contain 0.5 to 25 mass % of zinc and / or 0.5 to 30 mass % of nickel, with the balance being copper, and the balance of copper may contain inevitable impurities.
[0040] The shape of the conductive particles (B) is not particularly limited, and spherical, flaky (scaly), dendritic, and fibrous particles can be used, preferably spherical and / or dendritic (dendritic shape), and more preferably a combination of spherical and dendritic particles. When a spherical and dendritic shape is used in combination, excellent conductivity and bending resistance can be easily obtained. In addition, "spherical" conductive particles include not only roughly spherical conductive particles (atomized powder), but also roughly polyhedral spheres (reduced powder), indefinite shapes (electrolytic powder) and other roughly spherical conductive particles. In addition, "dendritic" refers to a shape having more than one dendritic protrusion protruding from the surface of the particle. The dendritic protrusion may be only a main branch without branches, or a shape in which a branch portion branches from the main branch and grows in a planar or three-dimensional manner.
[0041] The average particle size of the conductive particles (B) is preferably 1 to 20 μm. When the average particle size of the conductive particles is 1 μm or more, the dispersibility of the conductive particles becomes good, thereby preventing aggregation. When the average particle size of the conductive particles is 20 μm or less, excellent conductivity is easily obtained.
[0042] In this specification, the "average particle size of the conductive particles" refers to the number-based average particle size D50 (median diameter) measured by a laser diffraction / scattering method.
[0043] As the blocked isocyanate curing agent (C), one prepared by blocking polyisocyanate with a blocking agent can be used.
[0044] Examples of polyisocyanates include aliphatic diisocyanates such as hexamethylene diisocyanate (including trimers), tetramethylene diisocyanate, and trimethylhexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and 4,4'-methylenebis(cyclohexyl isocyanate); aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, and xylylene diisocyanate; and modified products of these diisocyanates (carbamates, carbodiimides, uretdiones, uretonimines, biuret and / or isocyanurate modified products, etc.). These may be used alone or in combination of two or more.
[0045] As examples of end-capping agents, monoalkyl (or aromatic) alcohols such as n-butanol, n-hexanol, 2-ethylhexanol, lauryl alcohol, phenol methanol, and methyl phenyl methanol can be preferably used; cellosolves such as ethylene glycol monohexyl ether and ethylene glycol mono-2-ethylhexyl ether; polyether-type diols at both ends such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol phenol; polyester-type diols at both ends obtained from diols such as ethylene glycol, propylene glycol, and 1,4-butanediol and dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, suberic acid, and sebacic acid; phenols such as p-tert-butylphenol and cresol; oximes such as dimethyl ketone oxime, methyl ethyl ketone oxime, methyl isobutyl ketone oxime, methyl amyl ketone oxime, and cyclohexanone oxime; and lactams represented by ε-caprolactam and γ-butyrolactam. These can be used alone or in combination of two or more.
[0046] The content of the blocked isocyanate curing agent (C) is not particularly limited and may be 60 to 120 parts by mass relative to 100 parts by mass of the binder component (A), but is more preferably 80 to 110 parts by mass.
[0047] Examples of the solvent (D) include glycol ethers such as diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, triethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, and dipropylene glycol dimethyl ether; alcohols such as terpineol, 2,2,4-trimethylpentane-1,3-diol monoisobutyrate, dihydroterpineol, and benzyl alcohol; and γ-butyrolactone. These may be used alone or in combination of two or more.
[0048] The content of the solvent (D) is not particularly limited, but is preferably 100 to 220 parts by mass, more preferably 140 to 180 parts by mass, based on 100 parts by mass of the binder component (A).
[0049] The conductive composition of the present invention is obtained by blending predetermined amounts of the above-mentioned components and thoroughly mixing them.
[0050] It should be noted that the conductive composition of the present invention may contain additives that have been conventionally added to conductive compositions of the same type within the scope of the present invention. Examples thereof include curing catalysts, defoamers, thickeners, tackifiers, fillers, anti-settling agents, colorants, antioxidants, plasticizers, ultraviolet absorbers, flame retardants, and the like.
[0051] The viscosity of the conductive composition of the present invention may be appropriately adjusted depending on the screen printer used. For example, the viscosity at a liquid temperature of 25° C. is preferably 20 to 600 Pa·s, more preferably 20 to 400 Pa·s, and even more preferably 20 to 300 Pa·s.
[0052] In addition, in this specification, "the viscosity of a conductive composition" means the viscosity measured at 25 degreeC and the rotation speed 1 rpm using the E type viscometer (cone and plate) spindle CPA-52Z manufactured by Brookfield Co., Ltd.
[0053] Example
[0054] Examples of the present invention are shown below, but the present invention is not limited to the following examples. In addition, unless otherwise specified, the blending ratio and the like are based on mass.
[0055] The respective components were mixed according to the formulations (parts by mass) shown in Tables 1 to 7 below to prepare conductive compositions.
[0056] Solid epoxy resin: solid bisphenol A type epoxy resin, DIC Corporation "HM-101", epoxy equivalent = 3200 to 3900 g / eq
[0057] Liquid epoxy resin 1: Dicyclopentadiene epoxy resin, "EP-4088L" manufactured by ADEKA Corporation
[0058] Liquid epoxy resin 2: Rubber-modified epoxy resin, ADEKA Corporation "EPR-1415-1"
[0059] Conductive particles 1: Spherical silver-coated copper particles with an average particle size of 2 to 3 μm
[0060] Conductive particles 2: Dendritic silver-coated copper particles with an average particle size of 4 to 6 μm
[0061] Blocked isocyanate curing agent (C): "DURANATE WM44-L70G" manufactured by Asahi Kasei Corporation, hexamethylene diisocyanate-based, NCO content = 5% by mass
[0062] Imidazole curing agent: "C11Z" manufactured by Shikoku Chemical Industry Co., Ltd., 2-undecyl imidazole
[0063] Thermal acid generator: "SI-110" manufactured by Sanshin Chemical Industry Co., Ltd., benzyl (4-hydroxyphenyl) (methyl) sulfonium hexafluorophosphate
[0064] ·Amine curing agent: "PN-H" manufactured by Ajinomoto Fine Chemicals Co., Ltd., epoxy resin amine adduct
[0065] Solvent 1: γ-butyrolactone
[0066] Solvent 2: Butyl Carbitol
[0067] Solvent 3: Dibutyl Carbitol
[0068] Solvent 4: Dipropylene glycol monomethyl ether
[0069] The volume resistivity, the number of pinholes, the viscosity, and the bending resistance of the obtained conductive composition were evaluated, and the results are shown in Tables 1 to 7. The evaluation method is as follows.
[0070] <Volume Resistivity>
[0071] A 290-mesh stainless steel screen printing plate was used to screen print on a 188-μm-thick PET film (length 100 mm, width 0.8 mm), and then heat cured at 130°C for 30 minutes to form a pattern. Next, the resistance value (R) between the two ends of the pattern was measured using a tester, and the cross-sectional area (S, cm 2 ) and length (L, cm) are used to calculate the volume resistivity using the following formula (1). If the volume resistivity is less than 1.2×10 -4 Ω·cm, the conductivity was evaluated to be excellent.
[0072] Volume resistivity = (S / L) × R (1)
[0073] <Number of pinholes>
[0074] A 400-mesh stainless steel screen printing plate was used to screen print on a 188 μm thick PET film, and then heat cured at 130°C for 30 minutes to form a coating. The obtained sample was photographed using an X-ray transmission device "Y.CheetahμHD" manufactured by YXLON International under the conditions of voltage 50 kV, current 80 μA, and power 4 W to obtain a transmission image. In the obtained transmission image, the number of pinholes generated in an area of 1 mm × 1 mm was counted at any position. If the number of pinholes in the specified area is 10 or less, it is evaluated as excellent in appearance.
[0075] <Viscosity>
[0076] The conductive composition was measured using an E-type viscometer (cone and plate type, manufactured by Brookfield Co., Ltd.) with a spindle of CPA-52Z, a measurement temperature of 25° C., and a rotation speed of 1 rpm.
[0077] <Bending resistance>
[0078] Use a 290-mesh stainless steel screen printing plate, screen print (length 100mm, width 0.8mm) on a PET film with a thickness of 100μm, and heat cure at 130°C for 30 minutes to form a pattern. The operation of making the coating film inside and bending 180° along a round rod with a bending radius of 1.5mm and then restoring it to a straight line is set as 1 time. After repeating 15 times, the resistance value between the two ends of the pattern is measured in the same way as above. Substitute the obtained result into the following formula to calculate the resistance value change rate. If the resistance value change rate is less than 100%, it is evaluated as excellent bending resistance. It should be noted that, with regard to bending resistance, only Comparative Example 1-1, Comparative Example 1-2, Example 1-1, and Example 5-1 are evaluated.
[0079] Resistance change rate (%) = ((resistance after bending - resistance before bending) / resistance before bending) × 100
[0080] [Table 1]
[0081] Comparative Example 1-1 Comparative Example 1-2 Example 1-1 Example 1-2 Comparative Examples 1-3 Solid epoxy resin 20 30 40 70 80 Liquid epoxy resin1 40 35 30 15 10 Liquid epoxy resin 2 40 35 30 15 10 Conductive particles 1 1623 1623 1623 1623 1623 Blocked isocyanate curing agent 101 101 101 101 101 Solvent 2 37 56 74 130 149 Solvent 3 20 20 20 20 25 Solvent 4 43 43 43 43 43 Volume resistivity (E-04Ω·cm) 1.18 0.89 0.79 0.89 1.29 Number of pinholes 42 15 6 1 0 Viscosity (Pa·s / 1rpm) 73.0 58.7 70.6 92.1 76.2 Bending resistance 134 109 61 - -
[0082] [Table 2]
[0083] Example 2-1 Example 2-2 Example 2-3 Embodiment 2-4 Solid epoxy resin 40 40 70 70 Liquid epoxy resin1 60 0 30 0 Liquid epoxy resin 2 0 60 0 30 Conductive particles 1 1623 1623 1623 1623 Blocked isocyanate curing agent 101 101 101 101 Solvent 2 74 74 130 130 Solvent 3 20 20 20 20 Solvent 4 43 43 43 43 Volume resistivity (E-04Ω·cm) 0.89 1.07 0.92 1.06 Number of pinholes 0 1 0 0 Viscosity (Pa·s / 1rpm) 56.4 127.0 76.2 111.9 Bending resistance - - - -
[0084] [Table 3]
[0085] Comparative Example 3-1 Example 3-1 Example 3-2 Comparative Example 3-2 Solid epoxy resin 52 52 52 52 Liquid epoxy resin1 24 24 24 24 Liquid epoxy resin 2 24 24 24 24 Conductive particles 1 1342 1471 2306 2660 Blocked isocyanate curing agent 101 101 101 101 Solvent 2 97 97 97 97 Solvent 3 6 8 37 49 Solvent 4 43 43 43 43 Volume resistivity (E-04Ω·cm) 1.60 1.05 0.53 0.50 Number of pinholes 8 1 6 20 Viscosity (Pa·s / 1rpm) 69.1 77.0 66.7 70.6 Bending resistance - - - -
[0086] [Table 4]
[0087] Comparative Example 4-1 Example 4-1 Example 4-2 Comparative Example 4-2 Solid epoxy resin 70 70 70 70 Liquid epoxy resin1 15 15 15 15 Liquid epoxy resin 2 15 15 15 15 Conductive particles 1 1623 1623 1623 1623 Blocked isocyanate curing agent 40 60 120 130 Solvent 2 130 130 130 130 Solvent 3 20 20 20 20 Solvent 4 17 26 51 56 Volume resistivity (E-04Ω·cm) 1.22 0.92 1.18 1.42 Number of pinholes 8 0 0 3 Viscosity (Pa·s / 1rpm) 188.1 152.4 77.0 71.1 Bending resistance - - - -
[0088] [Table 5]
[0089] | Example 5-1 Example 5-2 Example 5-3 Solid epoxy resin 52 52 52 Liquid epoxy resin1 24 24 24 Liquid epoxy resin 2 24 24 24 Conductive particles 1 1083 722 361 Conductive particles 2 722 1083 1444 Blocked isocyanate curing agent 101 101 101 Solvent 2 97 97 97 Solvent 3 28 31 39 Solvent 4 43 43 43 Volume resistivity (E-04Ω·cm) 0.64 0.68 0.66 Number of pinholes 2 1 3 Viscosity (Pa·s / 1rpm) 73.0 70.6 65.6 Bending resistance 39 - -
[0090] [Table 6]
[0091] Example 6-1 Example 6-2 Example 6-3 Solid epoxy resin 52 52 52 Liquid epoxy resin1 24 24 24 Liquid epoxy resin 2 24 24 24 Conductive particles 1 1083 1083 1083 Conductive particles 2 722 722 722 Blocked isocyanate curing agent 101 101 101 Solvent 2 97 97 97 Solvent 3 0 60 80 Solvent 4 43 43 43 Volume resistivity (E-04Ω·cm) 0.62 0.66 0.65 Number of pinholes 0 2 0 Viscosity (Pa·s / 1rpm) 271.5 46.8 27.8 Bending resistance - - -
[0092] [Table 7]
[0093] Comparative Example 7-1 Comparative Example 7-2 Comparative Example 7-3 Solid epoxy resin 60 60 60 Liquid epoxy resin1 20 20 20 Liquid epoxy resin 2 20 20 20 Conductive particles 1 1623 1623 1623 Blocked isocyanate curing agent - - - Imidazole curing agent 5 - - Thermal acid generator - 5 - Amine curing agent - - 10 Solvent 1 - 5 - Solvent 2 111 111 111 Solvent 3 64 64 64 Volume resistivity (E-04Ω·cm) 3.25 4.26 3.93 Number of pinholes 7 6 0 Viscosity (Pa·s / 1rpm) 63.5 54.8 61.1 Bending resistance - - -
[0094] As shown in Table 1, Comparative Examples 1-1 and 1-2 are examples in which the content of solid epoxy resin is less than the lower limit. Figure 1 , Figure 2 As shown in FIG. 1-1, FIG. 1-2, multiple circular pinholes are generated, and the appearance is poor. Figure 3 , Figure 4 As shown, almost no pinholes were confirmed. Moreover, the fewer the pinholes, the better the bending resistance. In addition, Comparative Example 1-3 is an example in which the content of the solid epoxy resin exceeds the upper limit, and the conductivity is poor.
[0095] From the results shown in Table 2, it is understood that the effects of the present invention can be obtained as long as the liquid epoxy resin contains at least one selected from the group consisting of alicyclic epoxy resins and rubber-modified epoxy resins.
[0096] As shown in Table 3, Comparative Example 3-1 is an example in which the content of the conductive particles is less than the lower limit, and the conductivity is poor. Comparative Example 3-2 is an example in which the content of the conductive particles exceeds the upper limit, and pinholes are generated, and the appearance is poor.
[0097] As shown in Table 4, Comparative Example 4-1 is an example in which the content of the blocked isocyanate curing agent is less than the lower limit, and the conductivity is poor. Comparative Example 4-2 is an example in which the content of the blocked isocyanate curing agent exceeds the upper limit, and the conductivity is poor.
[0098] From the results shown in Table 5, it is understood that more excellent conductivity can be obtained by using spherical conductive particles and dendritic conductive particles in combination as conductive particles.
[0099] From the results shown in Table 6, it can be seen that the viscosity of the conductive composition does not affect the generation of pinholes.
[0100] As shown in Table 7, when a curing agent other than the blocked isocyanate curing agent was used, the conductivity was poor.
Claims
1. A conductive composition comprising 1400 to 2500 parts by mass of conductive particles (B), 60 to 120 parts by mass of a blocked isocyanate curing agent (C) and a solvent (D) based on 100 parts by mass of a binder component (A) comprising 40 to 70 parts by mass of a solid bisphenol epoxy resin and 30 to 60 parts by mass of a liquid epoxy resin, The liquid epoxy resin includes at least one selected from the group consisting of alicyclic epoxy resins and rubber-modified epoxy resins.
2. The conductive composition according to claim 1, wherein The conductive particles (B) include spherical conductive particles and dendritic conductive particles.
3. The conductive composition according to claim 1 or 2, wherein The liquid epoxy resin comprises alicyclic epoxy resin and rubber modified epoxy resin.
Citation Information
Patent Citations
Method of treating successive signal samples and digital filter for carrying out the method
EP0014151A1
Thermosetting conductive paste composition
JP2013194169A